2013
DOI: 10.1182/blood-2012-05-431288
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of the PI3 kinase/Rap1/integrin αIIbβ3 pathway underlies ex vivo platelet hypoactivity in essential thrombocythemia

Abstract: Key Points• Platelets from essential thrombocythemia patients have an intrinsic impairment in the P13kinase/Rap1/integrin ␣IIb␤3 signaling pathway.• This explains the clinical observation that in vitro platelet aggregation is impaired in patients with essential thrombocythemia. IntroductionThe myeloproliferative disorders (MPDs) are a group of clonal hemopoietic disorders characterized by increased proliferation of one or more of the myeloid, erythroid, or megakaryocytic cell lineages. The MPDs include polycy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 51 publications
4
39
0
Order By: Relevance
“…This is consistent with patient studies, where impaired in vitro platelet function in ET patients was unrelated to JAK2 V617F status. 5 Thus, although JAK2 V617F in platelets may not directly affect platelet function and the prothrombotic phenotype, the possibility that it contributes at a later stage of the disease cannot be completely ruled out. These findings are also interesting in the light of recent publications describing a role for erythrocytes, leukocytes, and endothelial cells in hemostatic changes in MPN mouse models and the potential impact of JAK2 V617F on the prothrombotic potential of erythrocytes and endothelial cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with patient studies, where impaired in vitro platelet function in ET patients was unrelated to JAK2 V617F status. 5 Thus, although JAK2 V617F in platelets may not directly affect platelet function and the prothrombotic phenotype, the possibility that it contributes at a later stage of the disease cannot be completely ruled out. These findings are also interesting in the light of recent publications describing a role for erythrocytes, leukocytes, and endothelial cells in hemostatic changes in MPN mouse models and the potential impact of JAK2 V617F on the prothrombotic potential of erythrocytes and endothelial cells.…”
mentioning
confidence: 99%
“…2 Molecular changes in platelets, erythrocytes, leukocytes, and endothelial cells have all been suggested to contribute to the phenotype. [2][3][4][5] However, the mechanism underlying MPN-associated hemostatic changes still remains largely elusive. As the risk of thrombosis is strongly associated with the JAK2 V617F gene load in both ET and PV patients, the question that has fascinated many scientists in recent years is whether the JAK2 V617F mutation is the direct underlying cause of thrombosis and/or bleeding in MPN patients.…”
mentioning
confidence: 99%
“…16,[19][20][21] This dichotomy is also found in studies of intracellular signaling pathways relevant to platelet function: one group has described increased activation of Src kinases in ET platelets, 22 and another recently reported a dysfunction of the phosphatidylinositol 3-kinase (PI3K) pathway. 23 This bewildering variation in results is potentially due to the fact that the study of platelet function using samples from patients with PV and ET has been hampered by a number factors, including the following: (1) Clonality: Peripheral blood cells from patients with MPN have been shown to originate from an abnormal hemopoietic clone, 24 but in a significant proportion of patients, normal polyclonal hemopoiesis coexists alongside the abnormal clone. 25 This means that studies of peripheral blood platelets investigate the compound activities of platelets originating from both normal and malignant clones in varying ratios between patients.…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48] In keeping with these studies, a recent publication confirmed that TPO potentiation of platelet response to SFLLRN (a PAR-1 thrombin receptor agonist) was mediated by PI3K, leading to an increase in fibrinogen binding to integrin aIIbb3 but without an effect on P-selectin expression (ie, a granule secretion). 23 Interestingly, when looking at samples from patients with ET (with or without JAK2V617F), the same group made the exact reverse observation (ie, a decrease in the function of the PI3K/Rap1/ integrin aIIbb3 pathway, which could be secondary to medication). In contrast, our findings in this mouse model show an increase in fibrinogen binding as well as P-selectin expression in response to various agonists, in keeping with the increased hemostasis observed in the functional assays.…”
mentioning
confidence: 99%
“…This pathway is important in regulating α 1 bb3 integrin activity and platelet activation. 26 Platelet response to ADP and thrombin has been shown to be more pronounced in patients with MPN, especially those associated with the JAK2 mutation. 27 Platelet receptors for adhesion and aggregation are less expressed in chronic myeloproliferative patients compared to the control lot.…”
Section: Factorsmentioning
confidence: 99%